JENIS - JENIS ALGA YANG HIDUP PADA JARIAMUN (Potamogeton malaianus) DI DANAU SINGKARAK - Fatika Sari, Idra; Nursyahra, Nursyahra; Abizar, Abizar (STKIP PGRI Sumbar, 2014)
Â ABSTRACTÂ Algae are chorophil organism, almost all the cells were able to reproduce and algae epipitik also part perifitik algae that lives attached to various substrates such as attached to aquatic plants. West Sumatra is an area that has a lot of lakes, one of which is Singkarak lake. Singkarak like used as tourist areas and communities where livelihoods by Singkarak lake. Given the importance of the presence of algae in the water and the algae should be preserved. Research on algae in Singkarak lake epipitik conducted in December 2013. Purpose sampling metode to epipitik algae in Jariamun attache in Singkarak lake. This research was conducted by survey method (direct observation), sampling was performed at 3 stations. Station 1 in the Nagari Koto Singkarak subdistrict Saniang Baka Solok. This area is one of the breeding fish/cage as well as agricultural land in the Singkarak lake. Station 2 in the Regional District of Koto Singkarak Wall Nuts Solok district, regional household waste contamination. Station 3 in the Regional District of propagation Ombilin Tanah Datar, Batang River Watersheds Ombilin tipped on Singkarak lake. From this study found 25 species of algae epipitik 4 classes. In class Cyanophyceae found 3 types, Chlorophyceae 7 types,14 types Bacillaryophyceae, and Dinophyceae found 1 type. Algae is the most common of the 14 species Bacillaryophyceae class because the class Bacillaryophyceae conditions encountered in a variety of aquatic life and is one of the largest of algae group with high diversity and great abundance and wide distribution. While the least class Dinophyceae found as the most widespread distribution found in the oceans, so the Singkarak lake few found.